2000
DOI: 10.1016/s0014-5793(99)01762-7
|View full text |Cite
|
Sign up to set email alerts
|

Mildly oxidised low density lipoprotein induces platelet shape change via Rho‐kinase‐dependent phosphorylation of myosin light chain and moesin

Abstract: Oxidised low density lipoprotein (LDL) plays an important role in the pathogenesis of atherosclerosis. Here we demonstrate that mildly oxidised (mox) LDL engages the GTPase Rho and its effector molecule p160 Rho-kinase to induce phosphorylation of myosin light chain and of moesin leading to platelet shape change. Pretreatment of platelets with the selective Rho inhibitor C3-transferase from Clostridium botulinum or with the Rho-kinase inhibitor Y-27632 blocked mox-LDL-induced myosin light chain phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 27 publications
0
45
0
Order By: Relevance
“…Preliminary experiments indicated that mouse liver expresses low levels of LPA receptors, 4 which would minimize the local effects of autotaxin/lysoPLD-mediated LPA generation on liver tissue. The A1AT promoter (Ϫ1206 -ϩ44) was amplified by PCR from a Yac clone obtained from ATCC.…”
Section: Enpp2-tg and Enpp2mentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary experiments indicated that mouse liver expresses low levels of LPA receptors, 4 which would minimize the local effects of autotaxin/lysoPLD-mediated LPA generation on liver tissue. The A1AT promoter (Ϫ1206 -ϩ44) was amplified by PCR from a Yac clone obtained from ATCC.…”
Section: Enpp2-tg and Enpp2mentioning
confidence: 99%
“…The exposure of human platelets to LPA triggers shape change (3)(4)(5), fibronectin matrix assembly (6), and platelet-leukocyte interactions (7). LPA is also a weak activator of human platelet aggregation and potentiates the effects of other agonists such as ADP and epinephrine (3,8,9); although interestingly, platelets isolated from ϳ20% of normal donors are selectively unresponsive to LPA (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Low nanomolar concentrations of LPA induce shape change of washed platelets through LPA receptor-linked signal transduction pathways that involve the small guanosine triphosphatase (GTPase) Rho and the Rho-kinase-mediated stimulation of myosin light-chain phosphorylation. [7][8][9] In contrast, high micromolar concentrations of LPA are required to induce aggregation of platelet-rich plasma. [10][11][12] In the present study we investigated whether and through which mechanism LPA could induce platelet shape change and aggregation in whole blood.…”
Section: Introductionmentioning
confidence: 99%
“…The precise composition of the solutions has been described elsewhere. 15,19 Ca 2ϩ was buffered using 10 mmol/L EGTA. Normal relaxing solution for the experiment with membrane-permeabilized strips was of the following composition (mmol/L): potassium methanesulphonate, 74.1; magnesium methanesulphonate, 2; MgATP, 4.5; EGTA, 1; creatine phosphate, 10; PIPES, 30.…”
mentioning
confidence: 99%